The core international human rights treaties - United Nations (United Nations, 2014)
This publication reproduces the Universal Declaration of Human Rights, and the nine core international human rights treaties and their optional protocols in a user-friendly format to make them more accessible, in particular to government officials, civil society, human rights defenders, legal practitioners, scholars, individual citizens and others with an interest in human rights norms and standards.